Detecting aquatic and terrestrial biodiversity in a tropical estuary using environmental DNA - Polanco F., Andrea; Mutis Martinezguerra, Maria; Marques, Virginie; Villa‐Navarro, Francisco; Borrero Pérez, Giomar Helena; Cheutin, Marie‐Charlotte; Dejean, Tony; Hocdé, Régis; Juhel, Jean‐Baptiste; Maire, Eva; Manel, Stéphanie; Spescha, Manuel; et al. (Biotropica, 2021)
Estuaries are characterized by a tidal regime and are strongly influenced by hydrodynamics and host diverse and highly dynamic habitats, from fresh, brackish, or saltwater to terrestrial, whose biodiversity is especially difficult to monitor. Here, we investigated the potential of environmental DNA (eDNA) metabarcoding, with three primer sets targeting different regions of the mitochondrial DNA 12S ribosomal RNA gene, to detect vertebrate diversity in the estuary of the Don Diego River in Colombia. With eDNA, we detected not only aquatic organisms, including fishes, amphibians, and reptiles, but also a large diversity of terrestrial, arboreal, and flying vertebrates, including mammals and birds, living in the estuary surroundings. Further, the eDNA signal remained relatively localized along the watercourse. A transect from the deep outer section of the estuary, across the river mouth toward the inner section of the river, showed marked taxonomic turnover from typical marine to freshwater fishes, while eDNA of terrestrial and arboreal species was mainly found in the inner section of the estuary. Our results indicate that eDNA enables the detection of a large diversity of vertebrates and could become an important tool for biodiversity monitoring in estuaries, where water integrates information across the ecosystem. in Spanish is available with online material. Resumen Los estuarios se caracterizan por un régimen de mareas y están fuertemente influenciados por la hidrodinámica, albergando hábitats diversos y muy dinámicos, desde agua dulce, salobre o salada hasta terrestre, cuya biodiversidad es especialmente difícil de monitorear. Aquí investigamos el potencial del metabarcoding del ADN ambiental (eDNA), con tres pares de marcadores dirigidos a diferentes regiones del gen 12S del ADN mitocondrial en el ARN ribosomal, para detectar la diversidad de vertebrados en el estuario del río Don Diego en Colombia. Con el eDNA, detectamos no sólo organismos acuáticos, incluyendo peces, anfibios y reptiles, sino también una gran diversidad de vertebrados terrestres, arborícolas y voladores, incluyendo mamíferos y aves, que viven en los alrededores del estuario. Además, la señal de eDNA se mantuvo relativamente localizada a lo largo del curso de agua. Un transecto desde la sección exterior profunda del estuario, a través de la desembocadura del río hacia la sección interior del mismo, mostró un marcado cambio taxonómico desde los típicos peces marinos a los de agua dulce, mientras que el eDNA de las especies terrestres y arborícolas se encontró principalmente en la sección interior del estuario. Nuestros resultados indican que el eDNA permite detectar una gran diversidad de vertebrados y podría convertirse en una herramienta importante para el seguimiento de la biodiversidad en los estuarios, donde el agua integra la información de todo el ecosistema. eDNA enables the detection of a large diversity of vertebrates and could become an important tool for biodiversity monitoring in estuaries, where water integrates information across the ecosystem.